Factors influencing engagement in project-based learning among college EFL speakers - Zhong, Jianer; Ismail, Lilliati; Ahmad, Norhakimah Khaiessa (Society for Research and Knowledge Management, 2024)
There has been a surge in the popularity of project-based learning (PBL) as an instructional approach in foreign language education. However, despite the increasing body of research on students’ engagement in PBL, the focus on exploring engagement in PBL from a multi-dimensional perspective remains limited. Based on Reeve’s student engagement framework, an explanatory mixed methods design was employed to evaluate college English as a Foreign Language (EFL) speakers’ engagement (behavioural, emotional, cognitive and agentic) and elucidate the factors influencing engagement in PBL. For this study, 151 students from a polytechnic in China were recruited as participants, and a questionnaire was employed to examine the four dimensions of engagement in PBL among them. Additionally, semi-structured interviews were conducted with 10 students to understand their perspectives on how PBL has impacted their engagement levels. An analysis of the questionnaire data by descriptive statistics revealed that behavioural engagement ranked highest, followed by emotional, cognitive and agentic engagement. The interview data, analysed by thematic analysis, identified the factors influencing the four engagement dimensions of PBL, which were then categorised as positive (e.g., interest, group dynamics, topics and task types, etc.) and negative (e.g., weak English proficiency, introverted personality, fear of failure, etc.) factors. The findings provided insights into the four types of engagement and the factors influencing these dimensions. This study has educational implications for foreign language teachers as it will help them to find ways to engage college EFL students in PBL speaking activities and optimise the PBL environment.